Pengaruh Pembelajaran Kewirausahaan dan Praktik Kewirausahaan Terhadap Minat Berwirausaha (Studi pada Mahasiswa Jurusan Manajemen dan Akuntansi FEB Unisma Angkatan 2019) - Ayunda Anugrah Mustofa; Moh. Amin; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to examine the effect of entrepreneurship learning and entrepreneurship practice on student entrepreneurship interest in Malang. The sample size in this study was 89 out of 818 total population. The population of this study were students of the Faculty of Economics and Business, Islamic University of Malang, majoring in Management and Accounting class of 2019 who had taken advanced entrepreneurship courses and practicum. The sample used was simple random sampling. This study uses primary data obtained through distributing questionnaires and then processed and analyzed. The analysis method used is multiple linear regression analysis method carried out with the help of SPSS (Statistical Program for Social Science) version 21 so that the results of the analysis in this study are found in the form of entrepreneurship learning and entrepreneurship practice have a positive and significant effect on student entrepreneurship interest at the Faculty of Economics and Business, Islamic University of Malang. Keywords: Entrepreneurship learning, entrepreneurship practice, entrepreneurial interest